Development of the Pediatric Disability Inventory-Patient Reported Outcome (PEDI-PRO) measurement conceptual framework and item candidates. (3rd September 2018) - Kramer, Jessica M.; Schwartz, Ariel E.
Abstract: Background: To address the gap in patient reported outcome measures (PROMs) of functional performance appropriate for youth and young adults with developmental disabilities (DD) we developed the Pediatric Evaluation of Disability Inventory-Patient Reported Outcome (PEDI-PRO). Aim/Objective: We used a participatory process to: (1) Develop the measurement conceptual framework; (2) Identify discrete functional tasks to include in the PEDI-PRO; and (3) Refine item candidates. Methods: We collaborated with eight youth with DD over 33 months. These youth and university researchers explored the construct of functional performance, developed and refined items, and collected and analyzed data. We also conducted focus groups with youth with DD ( n  = 62) and rehabilitation professionals ( n  = 26), and consulted with PEDI measurement experts ( n  = 3). Results: Youth's understanding of their functional performance is embedded in their experiences participating in everyday life situations. We developed 78 Daily Activities, 65 Social/Cognitive, and 52 Mobility item candidates that are linked to 11 everyday life situations to assess discrete functional tasks important to youth with DD and rehabilitation professionals. Conclusion and Implications: As a result of our participatory development process, the PEDI-PRO's proposed conceptual framework and item candidates are grounded in the lived experience of youth with DD.